2016
DOI: 10.14744/nci.2015.07379
|View full text |Cite
|
Sign up to set email alerts
|

Primary ovarian leiomyoma in a postmenopausal woman: A case report

Abstract: Leiomyomas are benign neoplasms that can develop wherever smooth muscle is present. Primary leiomyomas of the ovary originate from smooth muscle cells of ovarian tissue and are rare, solitary tumors. Approximately 70 cases have been reported. They usually present in premenopausal women. The present case is a report of left ovarian leiomyoma in a postmenopausal woman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Although these tumors were benign and rare of them had abnormal histologic features, radical surgeries were usually done for their complete removal because the ovary might become almost completely absorbed by the tumor or just persist portions [50]. A common surgical approach was salpingo-oophorectomy or an oophorectomy with or without hysterectomy,but an ovary-preserving surgery should be suggested in young and fertility-sparing women [51].…”
Section: Resultsmentioning
confidence: 99%
“…Although these tumors were benign and rare of them had abnormal histologic features, radical surgeries were usually done for their complete removal because the ovary might become almost completely absorbed by the tumor or just persist portions [50]. A common surgical approach was salpingo-oophorectomy or an oophorectomy with or without hysterectomy,but an ovary-preserving surgery should be suggested in young and fertility-sparing women [51].…”
Section: Resultsmentioning
confidence: 99%
“…There is still no consensus on the origin of ovarian leiomyoma. Some scholars classify that it may originate from the blood vessels in the hilum of the ovary and the smooth muscle of the ovarian ligament, 7 whereas others point to the ovary cortex, ovary stroma 8 and other smooth muscle components in ovarian tumors. It is reported that about 78% of ovarian leiomyoma were associated with leiomyoma of uterus and they may have a common trigger 9 …”
Section: Discussionmentioning
confidence: 99%
“…Although these tumors were benign and rare of them had abnormal histologic features, radical surgeries were usually done for their complete removal because the ovary might become almost completely absorbed by the tumor or just persist portions [50]. A common surgical approach was salpingo-oophorectomy or an oophorectomy with or without hysterectomy,but an ovarypreserving surgery should be suggested in young and fertility-sparing women [51].…”
Section: Discussionmentioning
confidence: 99%